Administration and School Management: Adequacy Guidelines of Contemporary Capitalism - Flávio Reis Santos
The theme of this article despite the fact that the applicant in the context of research in the field of education, gain importance and relevance because of all the reflections set out in the framework of the debate about the conduct of public policies for education to the extent that we note that the old problems remain negatively affecting both educational and school management, as the quality of the training processes that happen inside it. The practical continuity in the formulation and implementation of such policies may reside in the constant adaptation of the education and public school to the heterogeneity of the capitalist market demands in proportion as the Brazilian government underwent orientation and World Bank interference in the administration of social issues.